Suprahepatic inferior vena cava stent placement for anastomotic stenosis - Zaid Nawaz, DO; Nicholas Gilbert, MD; Brendan Gontarz, MD; Edward T. Gifford, MD; Thomas Divinagracia, MD; Owen Glotzer, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
A 61-year-old female with previous liver transplantation was volume overloaded, requiring intubation and veno-venous extracorporeal membrane oxygenation. Workup was significant for mitral valve stenosis, for which she underwent repair. This was complicated by injury to the inferior vena cava with avulsion from the liver, which was reconstructed with bovine pericardium. Postoperatively, hemodynamic monitoring suggested poor venous return. She was taken for a venogram, demonstrating stenosis of the suprahepatic inferior vena cava, which was treated with placement of a bare metal self-expanding stent. This case report demonstrates an endovascular salvage technique for suprahepatic inferior vena cava stenosis after reconstruction during cardiac surgery.